The Aesthetics of the Contemporary Urban Landscape and its Implications for Well-Being - Betancourt, Axel Andrés Rodríguez (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2023)
In an increasingly urban world, more citizens are exposed to urban landscapes, including the aesthetics of these environments. Despite psychological research supporting the existence of a positive relationship between environmental aesthetics and well-being, the aesthetics of contemporary urban landscapes (UL) are subordinated to variables such as functionality and economic redeeming. The purpose was to study how citizens perceive contemporary UL in terms of aesthetics and how this relates to well-being. Using photographs of UL in an online questionnaire, quantitative and qualitative ratings of aesthetics and well-being were obtained of 63 participants. Results showed that contemporary UL were perceived as less aesthetic than traditional UL and associated with words suggesting a negative connotation. Analyses could not confirm a positive relationship between UL aesthetics and well-being. A qualitative analysis revealed a tendency to evaluate well-being negatively in relation to contemporary urban landscapes. As these findings suggest that aesthetics should be considered in urban planning, further research should focus on the possible relation between UL aesthetics and well-being.